2017
DOI: 10.1039/c6en00398b
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide shell mediated environmental remediation properties of nano zero-valent iron

Abstract: Nano zero-valent iron (nZVI) has attracted much more attention for its potential applications in the fields of environmental contaminant remediation and detoxification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(114 citation statements)
references
References 177 publications
3
111
0
Order By: Relevance
“…The fitting exercise produced R c = 19 nm and R t = 27 nm, which produces a shell length of 8 nm. This thickness is certainly consistent with an NZVI observed within 6 h after being synthesized [39]. This suggests that the behavior of the surface of NZVI should approximate the behavior of iron oxide nanoparticles, and also that the interactions of surfactants with the NZVI surface might be similar to that of surfactants with iron oxide.…”
Section: Dispersion Of Nzvi Suspensions With Surfactantssupporting
confidence: 80%
See 1 more Smart Citation
“…The fitting exercise produced R c = 19 nm and R t = 27 nm, which produces a shell length of 8 nm. This thickness is certainly consistent with an NZVI observed within 6 h after being synthesized [39]. This suggests that the behavior of the surface of NZVI should approximate the behavior of iron oxide nanoparticles, and also that the interactions of surfactants with the NZVI surface might be similar to that of surfactants with iron oxide.…”
Section: Dispersion Of Nzvi Suspensions With Surfactantssupporting
confidence: 80%
“…Zero-valent iron nanoparticles often have a layer of iron oxide, particularly when prepared by the aqueous borohydrate reduction used in this work. The thickness of the iron oxide layer of freshly prepared NZVI is close to 3 nm, and after 2 h of aging it can reach 6.5 nm, as determined via TEM images [39]. Yuvakkumar et al also indicated that the presence of iron oxide can be assessed via TEM images [40].…”
Section: Dispersion Of Nzvi Suspensions With Surfactantsmentioning
confidence: 99%
“…It has a small size for in situ injection and dispersion, large surface area, and high surface reactivity for metal‐ion reduction and immobilization. The unique core–shell structure imparts nZVI the versatile properties of reduction by metallic iron and sorption via iron oxides …”
Section: Introductionmentioning
confidence: 99%
“…Besides this fact, the catalytic activities of heterogeneous Fenton systems depend on numbers of other parameters; mainly solution pH, catalyst dosage, substrate concentration, H 2 O 2 concentration and reaction time. [9][10][11] In the recent years, magnetic nanoparticles with low iron dissolution have gained attention as a catalyst for the degradation of organic dyes due to their remarkable features such as a large specic surface area and easy recovery of catalyst. 12 The application of magnetic Fe 3 O 4 particles are limited in different media as it has less number of surface active functional groups, tend to aggregate, formation of clusters and iron leaching which reduce their activity and stability.…”
Section: Introductionmentioning
confidence: 99%